2015
DOI: 10.1098/rsos.150067
|View full text |Cite
|
Sign up to set email alerts
|

Rigidly foldable origami gadgets and tessellations

Abstract: Rigidly foldable origami allows for motion where all deflection occurs at the crease lines and facilitates the application of origami in materials other than paper. In this paper, we use a recently discovered method for determining rigid foldability to identify existing flat-foldable rigidly foldable tessellations, which are also categorized. We introduce rigidly foldable origami gadgets which may be used to modify existing tessellations or to create new tessellations. Several modified and new rigidly foldable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 25 publications
0
66
0
Order By: Relevance
“…Here, Guest fold is not rigid foldable as Lang et al (2015) showed. Also, Connelly et al proved (1997) that closed structure surrounded by triangulated surfaces cannot rigidly change its internal volume.…”
Section: Methods 21 Methods Of Creating Three Dimensionally Foldable Cmentioning
confidence: 90%
See 1 more Smart Citation
“…Here, Guest fold is not rigid foldable as Lang et al (2015) showed. Also, Connelly et al proved (1997) that closed structure surrounded by triangulated surfaces cannot rigidly change its internal volume.…”
Section: Methods 21 Methods Of Creating Three Dimensionally Foldable Cmentioning
confidence: 90%
“…The similar technique can be seen in the corner gadget by Evans (2015). After modification, stent fold and Guest fold can be combined like Fig.…”
Section: Structure B (Combination Of Stent Fold and Guest Fold) 321mentioning
confidence: 99%
“…Therefore, since we are interested in changing crease assignments to allow for defects, we must also incorporate the effect of the CP angles on the number of allowed crease assignments around a vertex into our models. Furthermore, aside from the importance of angles in flat-foldability and determining the number of valid crease assignments, flat-foldable CPs with the same connectivity and the same crease asignments but different angles can have very different folding properties, as seen in [23], where the Miura-ori, Barreto's Mars, the quadrilateral mesh, and the dual square twist CPs only differ in their angles, even though their resulting global foldings are quite different. We will not directly consider the resulting folding of the CP.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in complexity of origami shapes that provide engineering utility, computational methods for the design of origami structures have become essential for developments in this area of study [1,5,23]. As in most kinematic models for origami structures, current methods for origami design consider rigid faces and creased folds [24,25]. For example, one of the most well-known methods for origami design is the tree method [23].…”
Section: Introductionmentioning
confidence: 99%